KONTRIBUSI RETRIBUSI PASAR TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN MAMUJU - Rajab, Abdul (LPPM Universitas Muhammadiyah Mamuju, 2020)
Basically, an area's shopping is very dependent on the income of the region itself. Regional income is highly dependent on taxes and fees, one of the revenues from the retribution itself is market retribution. Therefore, the government must optimize revenue from market fees. This study aims to focus on analyzing the extent of the contribution of market levies to the Original Revenue in Mamuju Regency. This research aims to determine the role and development of the contribution of market levies on local revenue in Mamuju Regency. The analytical method used in this study is contribution analysis. Based on the analysis of contributions made, the results obtained are the contribution of market levies to the Original Revenue in Mamuju Regency during the period of 2014 to 2018 ranging from 1.52% to 1.1% with an average contribution of 1.29%. The largest contribution of market retribution to regional original income occurred in 2014 with a contribution of 1.52% and the smallest contribution occurred in 2017 with a contribution of 1.08%.